Estimating the NEMA characteristics of the J-PET tomograph using the GATE package. (10th August 2018) - Kowalski, P; Wiślicki, W; Shopa, R Y; Raczyński, L; Klimaszewski, K; Curcenau, C; Czerwiński, E; Dulski, K; Gajos, A; Gorgol, M; Gupta-Sharma, N; Hiesmayr, B; et al.
Abstract: A novel whole-body positron emission tomography (PET) system based on plastic scintillators is developed by the J-PET Collaboration. It consists of plastic scintillator strips arranged axially in the form of a cylinder, allowing the cost-effective construction of the total-body PET system. In order to determine the properties of the scanner prototype and optimize its geometry, advanced computer simulations were performed using the GATE (Geant4 application for tomographic emission) software. The spatial resolution, sensitivity, scatter fraction and noise equivalent count rate were estimated according to the National Electrical Manufacturers Association norm, as a function of the length of the tomograph, the number of detection layers, the diameter of the tomographic chamber and for various types of applied readout. For the single-layer geometry with a diameter of 85 cm, a strip length of 100 cm, a cross-section of 4 mm  ×  20 mm and silicon photomultipliers with an additional layer of wavelength shifter as the readout, the spatial resolution (full width at half maximum) in the centre of the scanner is equal to 3 mm (radial, tangential) and 6 mm (axial). For the analogous double-layer geometry with the same readout, diameter and scintillator length, with a strip cross-section of 7 mm  ×  20 mm, a noise equivalent count rate peak of 300 kcps was reached at 40 kBq cc −1 activity concentration, the scatter fraction is estimated to be about 35% and the sensitivity at the centre amounts to 14.9 cps kBq −1 . Sensitivity profiles were also determined.